A preliminary assessment of new bovine and avian tuberculin in cattle by intra-dermal tests and whole blood interferon gamma assay - YADAV, MINAKSHI; VERMA, RISHENDRA (The Indian Journal of Animal Sciences, 2016)
The present study reports ante-mortem diagnosis of bovine tuberculosis employing tuberculin test using a new tuberculin PPDB (M. bovis, 3/86) and interferon gamma assay in cattle whole blood culture stimulated using a commercial bovine IFN- γ assay kit. Dairy cattle (87) categorized in groups A, B and C were tested using tuberculin test and gamma interferon (IFN-γ). Fresh batches of bovine PPD (from M. bovis 3/86) and avian PPD (M. avium N–17) were prepared and were standardized by conforming to sterility, safety and potency. For tuberculin testing cervical single intradermal test (SIT) and caudal fold test (CFT) were performed using tuberculins at concentration of 1mg/ml and at the concentration of 0.3mg/ ml as a stimulating antigens in IFN-γ test. Out of 80 cattle (group A + B), 44 (55%) were reactor to tuberculin, 21 (26.25%) non reactor and 15 (18.75%) were inconclusive animals and by IFN-γ test 36 (45%) were M. bovis positive, 10 (12.5%) negative, 13 (16.25%) inconclusive and 21 (26.25%) were M. avium positive animals. In group C (not tuberculin tested) only 4 (57.14%) out of 7 cattle were positive. Relative sensitivity of IFN-γ test (63.88%) was higher than the tuberculin test (52.27%). Our study indicated that skin tests (CFT and SIT) and IFN-γ test can be used for successful control and eradication of bovine tuberculosis as IFN-γ test had higher sensitivity.